Pressure distribution from two different types of fabrics head garments with Silon-LTS® face mask for hypertrophic burn scar treatment - Fozi, Aiman; Salleh, Mohamed Najib; Khairul Azwan, Ismail (2015)
This study measures and analyses pressure generated from the two different fabrics used as head garments with a face mask made from Silon-LTS® (Low Temperature Splinting) underneath the head garment. A pressure sensor was used to measure the pressure generated using a head mannequin.In addition, modulus of elasticity is determined from the standard tensile test for fabric.The results shows that modulus of elasticity of the fabric gives the different pressure output and by applying the Silon-LTS® face mask underneath the head garments, the pressure increases at certain areas.